Conclusion of the Council for National Security of the Republic of Serbia Adopted on the Occasion of the Armed Conflict on the Territory of Ukraine That Began on 24 February 2022 - GJurovski, Marjan; Arnaudov, Mitko; Hadžić, Nikola (University "St. Kliment Ohridski"- Bitola, 2024)
: The aim of this paper is to try to explain the foreign policy of small states in contemporary and current international relations through the theory of neoclassical realism and on the example of the case study of the Republic of Serbia. The contribution of this paper in the theoretical sense testifies to the applicability of the theory of neoclassical realism in current international relations. When it comes to scientific knowledge, a kind of contribution to the theory itself is provided, bearing in mind the fact that it is about the application of the said theory to a small country, with limited economic, political, military and diplomatic capacities on the international level. In the context of small states, this work provides a contribution to the understanding of the creation of foreign policy and the adoption of foreign policy decisions by small states, and provides an explanation of how much room for maneuver they have in foreign policy action in current international relations.
Keywords: small states, foreign policy activities, national security, Serbia, neoclassical realism